INFORMATION TECHNOLOGIES AND THE ADAPTABILITY OF DEVELOPER COMPANIES - Matsala, Mykola; Slipchenko, Roman (SWorld-Ger Conference proceedings, 2025)
The article explores the role of information technologies in ensuring the adaptability of development companies in the context of the digital transformation of the construction industry. The main tools that contribute to strategic and operational flexibil